Technical Quality of Root Canal Treatment Performed By Undergraduate Dental Students - Dadresanfar, Bahareh; Mohammadzadeh Akhlaghi, Nahid; Vatanpour, Mehdi; Atef Yekta, Hojat; Baradaran Mohajeri, Ladan (Iranian Endodontic Journal, 2009)
INTRODUCTION: This study was carried out to evaluate the technical quality of root canal treatment (RCT) performed by undergraduate dental students at the Islamic Azad University in Tehran, Iran. MATERIALS AND METHODS: Four-hundred records of patients who had received RCT at faculty of dentistry, between the years 2004-2006 were evaluated. For each treated tooth at least three periapical x-rays were assessed: preoperative, working length measurement, and postoperative. Evaluation of root canal filling was based on two variables: length and density. The filling length was recorded as adequate, under- or overfilled. Density of filling was recorded as poor or adequate. Fillings with adequate length and density were recorded as acceptable. Detected iatrogenic errors were: ledge formations, root perforations, furcation perforations, strip perforations and presence of fractured instruments. Results were evaluated statistically using one-way ANOVA and Chi-square analysis. RESULTS: Out of the 400 teeth, 50.5% had at least one of the mentioned errors. Acceptable filling was observed in 32.5% of all studied teeth. Ledge was found in 17.5% of the teeth. Canal curvature was the most important factor associated with ledge formation (P<0.05). CONCLUSION: The technical quality of RCT performed by undergraduate dental students using step-back preparation and cold lateral condensation was classified as acceptable in 32.5% of the cases.